2013
DOI: 10.1128/aem.03254-12
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces lividans Blasticidin S Deaminase and Its Application in Engineering a Blasticidin S-Producing Strain for Ease of Genetic Manipulation

Abstract: c Blasticidin S is a peptidyl nucleoside antibiotic produced by Streptomyces griseochromogenes that exhibits strong fungicidal activity. To circumvent an effective DNA uptake barrier system in the native producer and investigate its biosynthesis in vivo, the blasticidin S biosynthetic gene cluster (bls) was engrafted to the chromosome of Streptomyces lividans. However, the resulting mutant, LL2, produced the inactive deaminohydroxyblasticidin S instead of blasticidin S. Subsequently, a blasticidin S deaminase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…SAM, L -arabinose, apramycin, spectinomycin, kanamycin and trimethoprim (TMP) were purchased from Sangon Biotech Co., Ltd. (Shanghai, China). S. lividans WJ2 contains the BS biosynthetic gene cluster and capable of producing blasticidin S ( Li et al, 2013 ), S. lividans WXK1 is derived from WJ2 by deletion of blsL gene, S. lividans WXK2 is derived from WXK1 complemented with blsL in an integrative plasmid pIB139. All Streptomyces strains (Supplementary Table S1 ) were cultivated at 30°C on Soy Flour-Mannitol (SFM) agar plates for sporulation, mycelia were grown in 10.3% TSBY (tryptic soy broth supplemented with 10.3% sucrose (wt/vol) and 1% yeast extract (wt/vol) medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAM, L -arabinose, apramycin, spectinomycin, kanamycin and trimethoprim (TMP) were purchased from Sangon Biotech Co., Ltd. (Shanghai, China). S. lividans WJ2 contains the BS biosynthetic gene cluster and capable of producing blasticidin S ( Li et al, 2013 ), S. lividans WXK1 is derived from WJ2 by deletion of blsL gene, S. lividans WXK2 is derived from WXK1 complemented with blsL in an integrative plasmid pIB139. All Streptomyces strains (Supplementary Table S1 ) were cultivated at 30°C on Soy Flour-Mannitol (SFM) agar plates for sporulation, mycelia were grown in 10.3% TSBY (tryptic soy broth supplemented with 10.3% sucrose (wt/vol) and 1% yeast extract (wt/vol) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, studies on BS biosynthesis have proceeded slowly since the cloning of BS biosynthetic gene cluster as gene deletion in BS native producer S. griseochromogenes was never successful. In order to bypass the restriction barrier, we engrafted BS biosynthetic gene cluster onto the chromosome of S. lividans and generated a BS heterologous producer S. lividans WJ2 ( Li et al, 2013 ), which here was used for in vivo study.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lower plants, Aclarubicin is produced by Streptomyces galilaeus actively used in the treatment of cancer (67) . Daunorubicin and its derivative doxorubicin are antitumour anthracycline antibiotics produced by Streptomyces peucetius (68) .Blasticidin is potent antifungal and cytotoxic peptidyl nucleoside antibiotic from Streptomyces griseochromogenes which plays a significant role in controlling prokaryotic and eukaryotic cell growth (69) . Chartreusin is a potent antitumor agent with a mixed polyketide-carbohydrate structure produced by Streptomyces chartreusis (70) .…”
Section: Methodsmentioning
confidence: 99%
“…The resistance to blasticidin S is conferred by expression of one of two genes, BSD from A. terreus or bsr from B. cereus, encoding blasticidin S deaminase (Housman et al, 2012;Li et al, 2013).…”
Section: Selection Of C Famata Strains Resistant To Blasticidinmentioning
confidence: 99%
“…Testing of O. polymorpha sensitivity to (b) aureobasidin and (c) mycophenolic acid [Colour figure can be viewed at wileyonlinelibrary.com] structure of blasticidin bound to the ribosome was used as a basis for the rational design of novel analogs with improved properties (Housman et al, 2012). It was shown that successful heterologous expression of blasticidin biosynthetic gene cluster in Streptomyces lividans HXY16 bypassed the difficult genetic manipulation of its native producer and led to the discovery of a blasticidin S deaminase from the S. lividans HXY16 (Li et al, 2013). Blasticidin did not affect the growth of Aspergillus flavus but specifically inhibited its aflatoxin production; however, its strong growth inhibitory activity was reported against E. coli and S. cerevisiae (Yoshinari, Sugita-Konishi, Ohnishi, & Terajima, 2017).…”
Section: Selection Of C Famata Strains Resistant To Blasticidinmentioning
confidence: 99%